Colostrum transfer of neutralizing antibodies against lumpy skin disease virus from vaccinated cows to their calves. Issue 6 (17th August 2018) - Agianniotaki, Eirini I.; Babiuk, Shawn; Katsoulos, Panagiotis‐Dimitrios; Chaintoutis, Serafeim C.; Praxitelous, Anastasia; Quizon, Kaye; Boscos, Constantinos; Polizopoulou, Zoe S.; Chondrokouki, Eleni D.; Dovas, Chrysostomos I.
Abstract: The objective of the present study was to access the titres and duration of maternally derived neutralizing antibodies against lumpy skin disease virus (LSDV) in calves born to immunized dairy cows. The study was conducted in a Greek farm of 200 Holstein cows which were immunized with a homologous Neethling strain‐based attenuated vaccine. Composite colostrum samples were obtained from 18 selected cows at the day of calving. Blood samples were obtained from each dam‐calf pair prior to the first colostrum feeding and from the calves successively on the third day after calving and on monthly intervals thereafter, until day 150. Passive transfer of antibodies in calves was evaluated by determining the levels of total protein in serum samples collected on day 3. Neutralizing antibody (NAb) titres against LSDV in colostrum and serum samples were determined by virus neutralization test. Colostrum NAb titres >1:160 were associated with the presence of NAbs in serum from calves 3 days after birth. Out of the 18 calves, which received colostrum with NAbs, 16 (88.9%) had detectable NAbs in their serum. Thereafter, a declining percentage of calves with detectable serum NAbs was recorded (38.5% on day 90 and 0% on days 120 and 150). Only calves with high NAb titres on day 3 had detectable serum NAbs until day 90 after calving. Thus, a significant number of calves were not protected by maternal antibodies against the disease after the age of 3 months and likely even after the age of 2 months. The findings of the present study substantiate that current recommendation for vaccination can be amended, so as to minimize the susceptible bovine population and enable optimized LSD prevention and eradication.